Exploiting Common Aspects of Obesity and Alzheimer’s Disease - Tabassum, Sidra; Misrani, Afzal; Yang, Li (Frontiers in Human Neuroscience, 2020)
Alzheimer’s disease (AD) is an example of age-related dementia, and there are still no known preventive or curative measures for this disease. Obesity and associated metabolic changes are widely accepted as risk factors of age-related cognitive decline. Insulin is the prime mediator of metabolic homeostasis, which is impaired in obesity, and this impairment potentiates amyloid-β (Aβ) accumulation and the formation of neurofibrillary tangles (NFTs). Obesity is also linked with functional and morphological alterations in brain mitochondria leading to the brain insulin resistance (IR) and memory deficits associated with AD. In addition, increased peripheral inflammation and oxidative stress due to obesity are the main drivers that increase an individual’s susceptibility to cognitive deficits, thus doubling the risk of AD. This enhanced risk of AD is alarming in the context of a rapidly increasing global incidence of obesity and overweight in the general population. In this review, we summarize the risk factors that link obesity with AD and emphasize the point that the treatment and management of obesity may also provide a way to prevent AD.